Impact of mobile banking on traditional banking practices in Zimbabwe - Mavhiki, Severino; Nyamwanza, Tonderai; Shumba, Life (International Journal of Economics, Commerce and Management, 2015)
The motivation behind this study was the rapid changes that were happening in the banking industry with the coming in of mobile banking, but a gap remained in addressing the implications of this innovation on traditional banking practices in Zimbabwe. It was established that though customers have remained loyal to banks, the banks have not been able to grow their businesses as a result of the advent of mobile banking, and instead of them seeking collaboration with the telecoms they chose to be confrontational, and lobbying for legislation that regulates mobile operators. Most banks introduced their own mobile banking products but these did not deliver full potential as they are limited to account holders only. Commercial banks should develop growth strategies along the mobile banking business model.